Spatial electric load forecasting using a local movement approach - Carreno, E. M. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
An agent based model for spatial electric load forecasting using a local movement approach for the spatiotemporal allocation of the new loads in the service zone is presented. The density of electrical load for each of the major consumer classes in each sub-zone is used as the current state of the agents. The spatial growth is simulated with a walking agent who starts his path in one of the activity centers of the city and goes to the limits of the city following a radial path depending on the different load levels. A series of update rules are established to simulate the S growth behavior and the complementarity between classes. The results are presented in future load density maps. The tests in a real system from a mid-size city show a high rate of success when compared with other techniques. The most important features of this methodology are the need for few data and the simplicity of the algorithm, allowing for future scalability. © 2009 IEEE.
Keywords: Agent based models; Distribution planning; Knowledge extraction; Land use; Spatial electric load forecasting; Activity centers; Agent-based model; Consumer class; Electrical load; Growth behavior; High rate; Load density; Load levels; Spatial growth; Electric load distribution; Electric loads; Intelligent systems; Multi agent systems; Electric load forecasting